Metacognitive Skills in Mathematics Learning: A Systematic Review of Literature - Kathayat, Bhakta Bahadur (Journal of Musikot Campus, 2024)
The goal of mathematical learning strategies is to create highly competent skills people with various problem-solving processes. Nonetheless, conceptual grasp remains a difficult issue in mathematics. So, the review article is about metacognitive skills and mathematical problem-solving. This paper aims to determine the impact of metacognitive skills on problem-solving skills in mathematics learning in a metacognitive learning strategy. metacognition skills are an important factor in the problem-solving process in mathematics. The review of thirteen articles related to metacognitive strategy and problem-solving in mathematics learning found that the metacognitive skills regarding planning, monitoring, and evaluation affect the development of a more profound comprehension of the learning process in mathematics, empowering them to become more effective and independent learners in mathematics learning. Additionally, these skills have a significant role in understanding the problem, making a plan, carrying out the plan, and looking backward to the solution in the problem-solving of mathematics learning.